Maritime Industry Development and Social Exclusion of Local Communities in Coastal Areas - Gabriela Vanesa Mutiarani; Cristian Gotama (Journal of Economic Growth and Development Review, 2026)
The development of the maritime industry is one of the important strategies in supporting national economic growth, especially in archipelagic countries such as Indonesia. This development includes the development of ports, coastal industrial estates, and marine infrastructure designed using a marine engineering approach. However, in addition to having a positive impact in the form of increasing economic activity and regional connectivity, the development of the maritime industry also has the potential to cause social exclusion for coastal local communities. Social exclusion can occur due to reduced public access to marine resources, changes in livelihoods, and changes in the coastal environment due to the development of marine infrastructure such as breakwater and reclamation. From the perspective of marine engineering, coastal development not only emphasizes the technical aspects of construction, but must also consider environmental and social impacts through the application of sustainable development concepts and integrated coastal area management. Therefore, the integration of marine engineering planning, environmental protection, and local community empowerment is key in creating sustainable and inclusive maritime industry development.